Peran Pembelajaran Pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Era Globalisasi dalam Mencegah Perilaku Menyimpang Siswa di SMAN II Kabupaten Bulukumba - Andi Baso; Nasrun Hasan (JED (Jurnal Etika Demokrasi), 2018)
This study aims to determine the causes of deviant behavior, the role of learning Citizenship Education in the era of globalization in preventing the occurrence of deviant behavior of students in SMU 11 Bulukumba and the inhibiting factors of learning Citizenship Education in the era of globalization in preventing deviant behavior of students at SMU 11 Bulukumba. This type of research is qualitative descriptive research. This research was conducted at SMU 11 Bulukumba. Data sources used are primary data in the form of interviews and secondary data in the form of documents. The population in the study was the vice principal, BK teacher, PKn teacher and also students at SMU 11 Bulukumba. Data collection techniques used are interview techniques, observation and documentation. The research data were analyzed qualitatively descriptive. The results of this study indicate that (1) The causes of deviant behavior at SMAN 11 Bulukumba are social media, social, family and broken home, (2) Learning Citizenship Education has an important role in preventing students' deviant behavior. This is proven by using goals, learning materials, learning methods and strategies, good media and evaluation to make students not affected by the effects of globalization and (3) inhibiting factors for learning Citizenship Education is the mindset of students themselves, decreasing student motivation because more often dominated by users of social media such as Facebook during each class, so students become unfocused in learning the attitudes of material on Citizenship Education.Keywords : Learning Citizenship Education, Globalization, Deviant Behavior.